2017
DOI: 10.5194/angeo-35-885-2017
|View full text |Cite
|
Sign up to set email alerts
|

Bursty emission of whistler waves in association with plasmoid collision

Abstract: Abstract.A new mechanism to generate whistler waves in the course of collisionless magnetic reconnection is proposed. It is found that intense whistler emissions occur in association with plasmoid collisions. The key processes are strong perpendicular heating of the electrons through a secondary magnetic reconnection during plasmoid collision and the subsequent compression of the ambient magnetic field, leading to whistler instability due to the electron temperature anisotropy. The emissions have a bursty natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…It is believed that FRs play an important role in the macroscopic and microscopic physical processes occurring during magnetic reconnection, such as modulation of reconnection rates and electron accelerations (e.g., Chen et al, ; Daughton et al, , ; Drake et al, ; Fu, Cao, et al, ; Fu, Khotyaintsev, et al, ; Fujimoto, ). Simulations have shown that the electrons can be accelerated by the contracting of FRs via the Fermi acceleration mechanism (Drake et al, ; Fu et al, ), by the reconnection electric field in the secondary FRs (Oka, Fujimoto, et al, ), and by the coalescence of FRs (Oka, Phan, et al, ; Pritchett, ; Zhou et al, ) in the reconnection region.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that FRs play an important role in the macroscopic and microscopic physical processes occurring during magnetic reconnection, such as modulation of reconnection rates and electron accelerations (e.g., Chen et al, ; Daughton et al, , ; Drake et al, ; Fu, Cao, et al, ; Fu, Khotyaintsev, et al, ; Fujimoto, ). Simulations have shown that the electrons can be accelerated by the contracting of FRs via the Fermi acceleration mechanism (Drake et al, ; Fu et al, ), by the reconnection electric field in the secondary FRs (Oka, Fujimoto, et al, ), and by the coalescence of FRs (Oka, Phan, et al, ; Pritchett, ; Zhou et al, ) in the reconnection region.…”
Section: Introductionmentioning
confidence: 99%
“…This confirms the case study by Khotyaintsev et al (2011), where the location of the whistler source at the center of the current sheet has been determined from multispacecraft observations of the wave Poynting flux. However, in more complex reconnection configurations, as in the case of plasmoid coalescence (secondary reconnection), the source of pile-up driven whistlers can be located away from the center of the main current sheet (Fujimoto, 2017).…”
Section: Whistlersmentioning
confidence: 99%
“…Multipoint spacecraft observations showed that the magnetic structures associated with the earthward and tailward bulk flows can be formed at ion and sub-ion kinetic scales and/or have very thin fronts/boundaries with a characteristic thickness of the order of ion gyroradius or less (Sergeev et al 2009;Balikhin et al 2014;Huang et al 2016;Grigorenko et al 2018;He et al 2021). These structures can be the sites of strong energy dissipation (e.g., Drake et al 2006;Fu et al 2006;Oka et al 2010;Huang et al 2019), which affects the particle velocity distribution functions and causes the generation of various types of electromagnetic and electrostatic wave modes (e.g., Zhang et al 1999;Le Contel et al 2009;Tenerani et al 2013;Fujimoto 2014Fujimoto , 2017Zhang & Angelopoulos 2014;Grigorenko et al 2016;Huang et al 2016;Wang et al 2016;Guo et al 2021;Pickett 2021).…”
Section: Introductionmentioning
confidence: 99%